2016
DOI: 10.5194/acp-16-12829-2016
|View full text |Cite
|
Sign up to set email alerts
|

Dry season aerosol iron solubility in tropical northern Australia

Abstract: Abstract. Marine nitrogen fixation is co-limited by the supply of iron (Fe) and phosphorus in large regions of the global ocean. The deposition of soluble aerosol Fe can initiate nitrogen fixation and trigger toxic algal blooms in nitrate-poor tropical waters. We present dry season soluble Fe data from the Savannah Fires in the Early Dry Season (SAFIRED) campaign in northern Australia that reflects coincident dust and biomass burning sources of soluble aerosol Fe. The mean soluble and total aerosol Fe concentr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 109 publications
9
45
0
Order By: Relevance
“…In this scenario, we are comparing data from the Misison Beach with results of FFeS of Australian aerosols and soils to get comparision in terms of ocean fetrilisation potential and sources. The FFeS results reported in this section are similar to data reported by Winton et al [28] for aerosols collected at a coastal site in the Northern Territory (Australia) (2%-12%) and lie in the lower range of solubilities observed in Tasmania (0.5%-56%) [29]. The labile fraction of Fe in aerosols collected at Mission Beach is similar to those reported in aerosols collected at sea during the same period (4%- Reported values for Fe solubilities around Australia are sparse and variable between sampling sites.…”
Section: Iron Solubilitysupporting
confidence: 91%
See 2 more Smart Citations
“…In this scenario, we are comparing data from the Misison Beach with results of FFeS of Australian aerosols and soils to get comparision in terms of ocean fetrilisation potential and sources. The FFeS results reported in this section are similar to data reported by Winton et al [28] for aerosols collected at a coastal site in the Northern Territory (Australia) (2%-12%) and lie in the lower range of solubilities observed in Tasmania (0.5%-56%) [29]. The labile fraction of Fe in aerosols collected at Mission Beach is similar to those reported in aerosols collected at sea during the same period (4%- Reported values for Fe solubilities around Australia are sparse and variable between sampling sites.…”
Section: Iron Solubilitysupporting
confidence: 91%
“…Elements were divided into three groups based on their median EF into (1) low, EF < 2, (2) moderate, 2 ≤ EF < 10, and (3) high, EF ≥ 10. This classification is similar to the one applied by Winton et al [28] and Buck at al. [81] for an aerosol samples origin investigation.…”
Section: Enrichment Factormentioning
confidence: 63%
See 1 more Smart Citation
“…ATARS provides an ideal location to further investigate BB-derived fractional iron solubility at the source. The results from this study can be found in Winton et al (2016) and show that soluble iron concentrations from BB sources are significantly higher than those observed in Southern Ocean baseline air masses from the Cape Grim Baseline Air Pollution Station, Tasmania, Australia (Winton et al, 2015). Aerosol iron at SAFIRED was a mixture of fresh BB, mineral dust, sea spray and industrial pollution sources.…”
Section: Biomass Burning Aerosol Chemistrymentioning
confidence: 67%
“…Furthermore the fractional solubility of aerosol iron and other trace metals during SAFIRED were investigated in Winton et al (2016). The fractional iron solubility is an important variable determining iron availability for biological uptake in the ocean.…”
Section: Biomass Burning Aerosol Chemistrymentioning
confidence: 99%